Redes de Bragg em fibras óticas multimodo: análise numérica e experimental da sensibilidade ao índice de refração - Kuhne, Jean Filipe (2016)
In this work are reported the experimental and numerical results of a refractometer based on fiber Bragg gratings produced on multimode optical fibers. The performance of the gratings inscribed in multimode optical fibers is compared with the gratings inscribed in single mode optical fibers. In order to become sensitive to the external refractive index, the gratings were subdued to a chemical etching process, after which the single mode fiber presented a (18.08 ± 0.01) m diameter while the multimode fiber presented a (17.10 ± 0.10) m diameter. The results of this study showed that the gratings inscribed in multimode optical fibers presented a higher sensitivity to the external refractive index, and a broader dynamic range as well, when compared with the gratings inscribed in single mode optical fibers. Experimental results showed a 41.9 nm/RIU sensitivity for gratings inscribed in multimode optical fibers and a 1.3 nm/RIU sensitivity for gratings inscribed in single mode optical fibers, being both fibers exposed to a 1.4656 external refractive index. Multimode optical fibers provided an increase in the system sensitivity, and a mechanical robustness improvement as well, due to the higher optical fibers diameters employed when compared with single mode optical fibers with similar sensitivities. The devices were used to determine the vegetal oil concentration of oil-biodiesel blends, which stands as a quality parameter for the fuel production and distribution. The results showed that the mode 1 allowed a resolution of 2.11% v/v for 0.00 % of oil concentration and 0.28 % v/v when oil concentration was 70.00% v/v. Analysis performed with mode 2 showed a resolution of 1.37% v/v for 0.00 % of oil concentration and 0.13 % v/v when oil concentration was 60.51% v/v.